Circulating biomarkers for early detection and clinical management of colorectal cancer. (October 2019) - Marcuello, María; Vymetalkova, Veronika; Neves, Rui P.L.; Duran-Sanchon, Saray; Vedeld, Hege Marie; Tham, Emma; van Dalum, Guus; Flügen, Georg; Garcia-Barberan, Vanesa; Fijneman, Remond JA.; Castells, Antoni; Vodicka, Pavel; et al.
Abstract: New non-invasive approaches that can complement and improve on current strategies for colorectal cancer (CRC) screening and management are urgently needed. A growing number of publications have documented that components of tumors, which are shed into the circulation, can be detected in the form of liquid biopsies and can be used to detect CRC at early stages, to predict response to certain therapies and to detect CRC recurrence in a minimally invasive way. The analysis of circulating tumor DNA (ctDNA), tumor-derived cells (CTC, circulating tumor cells) or circulating microRNA (miRNA) in blood and other body fluids, have a great potential to improve different aspects of CRC management. The challenge now is to find which types of components, biofluids and detection methods would be the most suitable to be applied in the different steps of CRC detection and treatment. This chapter will provide an up to date review on ctDNA, CTCs and circulating miRNAs as new biomarkers for CRC, either for clinical management or early detection, highlighting their advantages and limitations.